Ultraliberal inflection and federative dynamics in Brazil (Desarrollo, Estado y Espacio, 2022)
Brazilian society has been facing a new historical cycle since the second half of the last decade, whose most relevant characteristic is the adoption of the neoliberal reforms of the 1990s on a more systemic basis, forming an ultra-liberal inflection – a concept that refers to the meaning of the process (inflection) and its content (ultraliberal). The purpose of the article is to discuss the implications of these transformations for the Brazilian federative regime. The argument is that the ultra-liberal inflection has altered key elements of the Brazilian federal system, thus engendering a new federative dynamic, distinct from the one that has prevailed since the 1988 Constitution.
Keywords: Federalism; Federal dynamics; Federal institutions; Neoliberalism